Dynamics of Haematopoietic Stem Cells Model - Julia Stoberova (Communications - Scientific letters of the University of Zilina, 2012)
The article deals with the haematopoietic stem cells model with delay introduced by M. C. Mackey [1]. Our aim is to establish the new conditions under which the equilibria of the model are stable or unstable. The model without delay is also investigated.